A static verification framework for message passing in Go using behavioural types - Lange, Julien; Ng, Nicholas; Toninho, Bernardo; Yoshida, Nobuko (2018 IEEE/ACM 40th International Conference on Software Engineering (ICSE), 2018)
The Go programming language has been heavily adopted in industry as a language that efficiently combines systems programming with concurrency. Go's concurrency primitives, inspired by process calculi such as CCS and CSP, feature channel-based communication and lightweight threads, providing a distinct means of structuring concurrent software. Despite its popularity, the Go programming ecosystem offers little to no support for guaranteeing the correctness of message-passing concurrent programs. This work proposes a practical verification framework for message passing concurrency in Go by developing a robust static analysis that infers an abstract model of a program's communication behaviour in the form of a behavioural type, a powerful process calculi typing discipline. We make use of our analysis to deploy a model and termination checking based verification of the inferred behavioural type that is suitable for a range of safety and liveness properties of Go programs, providing several improvements over existing approaches. We evaluate our framework and its implementation on publicly available real-world Go code.